The Role of Corporate Governance and Financial Performance in Influencing Stock Returns through Dividend Policy: Evidence from the Automotive Subsector in Indonesia (2014–2023) - Shabrina, Hafiyya; Gursida, Hari; Hardiyanto, Arief Tri (Asosiasi Ahli Administrasi Indonesia, 2025)
This study investigates the role of corporate governance and financial performance, as measured by Good Corporate Governance (GCG), Current Ratio (CR), Return on Equity (ROE), and Debt to Equity Ratio (DER), in influencing stock returns, with dividend policy acting as a mediating variable. Using panel data from 12 automotive and component manufacturing firms listed on the Indonesia Stock Exchange over the period 2014 to 2023, the study adopts a quantitative approach, employing panel regression techniques and the Sobel test for mediation analysis. The findings reveal that some of the research variables have a statistically significant and positive effect on stock returns, while one shows no significant direct impact. All the independent variables significantly influence dividend policy, which in turn has a positive and significant effect on stock returns. Furthermore, the mediation analysis confirms that dividend policy significantly mediates the relationship between the research variables and stock returns. These results highlight the important role of dividend policy as a transmission mechanism through which internal company factors affect market performance. The findings support both signaling and agency theories and offer practical implications for corporate managers and investors in aligning governance and financial strategies to maximize shareholder value.